(3JgPjH GddZIs - (3eMeO Hf CMeO Hf GdCRgQj GdgQhj, CHh efUhQ,J (B370 (3g` s ((3Ydi Hf eMeO Hf UObI GdNaGLi GdMfai s)
(3ChdgG (B:s
(3jHJOF HCHhGH GdMGA hGdJGA s
(3BNQgG (B:s
(3hGdWgGQI GSe jbhe Ydi GdWgQ HGdeGA ddGSJfLGA hGdhVhA BNQ GdLRA GdQGHY ef cJGH JgPjH GddZI ddGRgQi hGdMeO ddg QH GdYGdejf s
(3ef GdCUd GdPi bGHdg GdTjNGf GdYGdeGf GHf GdNTGH hGHf GdYUGQ QMegeG Gddgs
(3Ydjg Jedc HGSe GHQGgje Hf GdedG GdMdHis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B230s
Keywords: (3GddZIs